Why and when organizational culture fosters affective commitment among knowledge workers: the mediating role of perceived psychological contract fulfilment and moderating role of organizational tenure. Issue 6 (26th March 2018) - Lee, Jean; Chiang, Flora F. T.; van Esch, Emmy; Cai, Zhenyao
Abstract: Drawing on Denison and Mishra (1995)'s framework of organizational culture, this study examines why and when organizational culture is related to knowledge workers' affective commitment. Data were collected from 640 employees working in three high-technology companies in China. The findings indicate that the relationship between organizational culture and affective commitment is mediated by perceived psychological contract fulfilment. In addition, organizational tenure moderates the relationship between two external dimensions (i.e. adaptability and mission) of organizational culture and perceived psychological contract fulfilment. This study extends the current theoretical framework of organizational culture by demonstrating the underlying mechanism and the boundary condition of the relationship between organizational culture and affective commitment. The findings also provide practical implications for international managers to design appropriate human resource management policies and practices in China.